A REVIEW OF IMAGE SECURITY WITH STEGANOGRAPHY USING DCT COEFFICIENT AND ENCRYPTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the mid 1998s the rise of the internet & multimedia techniques has prompted increasing interest in hiding data in digital media. Early research concentrated on watermarking to protect copyrighted multimedia products. In today’s growing world Image data security is the essential portion in communication and multimedia world. The least significant-bit (LSB) based technique is one of the popular for steganography. Medium integrity is an important issue in steganography, whenever one media is hidden into other the originality of cover media should not affect. Image Security with Steganography using DCT Coefficient and Encryption providing security of data & helps to avoid third party access of data is the challenging world.